Reliability and Validity of the Functional Movement Screen™ with a Modified Scoring System for Young Adults with Low Back Pain - Khalid Alkhathami; Yousef Alshehre; Sharon Wang-Price; Kelli Brizzolara (North American Sports Medicine Institute, 2021)
# Background Low back pain (LBP) is one of the most common complaints in individuals who seek medical care and is a leading cause of movement impairments. The Functional Movement Screen (FMS™) was developed to evaluate neuromuscular impairments during movement. However, the reliability and validity of the FMS™ have not yet been established for the LBP population because of a limitation of its original scoring system. # Purpose The purposes of this study were to determine the reliability and validity of the FMS™ with a modified scoring system in young adults with and without LBP. The FMS™ scores were modified by assigning a zero score only when there was an increase in LBP during the FMS™, not simply for the presence of pain, as in the original FMS™ scoring system. # Study Design Reliability and validity study. # Methods Twenty-two participants with LBP (8 males and 14 females, 26.7 ± 4.68 years old) and 22 age- and gender-matched participants without LBP (26.64 ± 4.20 years old) completed the study. Each participant performed the FMS™ once while being scored simultaneously and independently by two investigators. In addition, each participant's FMS™ performance was video-recorded and then was scored by another two investigators separately. The video-recorded performance also was scored twice six weeks apart by the same investigator to determine intra-rater reliability. # Results The results showed excellent inter-rater and intra-rater reliability of the FMS™ composite score with intraclass correlation coefficients ranging from 0.93 to 0.99 for both groups. In addition, the LBP group scored significantly lower than the group without LBP (*p* = 0.008). # Conclusions The results indicate that the FMS™ is able to distinguish between individuals with and without LBP, and that it could be a useful test for clinicians to quantify movement quality and to assess movement restrictions in individuals with LBP. # Levels of Evidence 2b.